Extracellular HSP110 skews macrophage polarization in colorectal cancer. (2nd July 2016) - Berthenet, Kevin; Boudesco, Christophe; Collura, Ada; Svrcek, Magali; Richaud, Sarah; Hammann, Arlette; Causse, Sebastien; Yousfi, Nadhir; Wanherdrick, Kristell; Duplomb, Laurence; Duval, Alex; Garrido, Carmen; et al.
ABSTRACT: HSP110 is induced by different stresses and, through its anti-apoptotic and chaperoning properties, helps the cells to survive these adverse situations. In colon cancers, HSP110 is abnormally abundant. We have recently showed that colorectal cancer (CRC) patients with microsatellite instability (MSI) had an improved response to chemotherapy because they harbor an HSP110 inactivating mutation (HSP110DE9). In this work, we have used patients' biopsies and human CRC cells grown in vitro and in vivo (xenografts) to demonstrate that (1) HSP110 is secreted by CRC cells and that the amount of this extracellular HSP110 is strongly decreased by the expression of the mutant HSP110DE9, (2) Supernatants from CRC cells overexpressing HSP110 or purified recombinant human HSP110 (LPS-free) affect macrophage differentiation/polarization by favoring a pro-tumor, anti-inflammatory profile, (3) Conversely, inhibition of HSP110 (expression of siRNA, HSP110DE9 or immunodepletion) induced the formation of macrophages with a cytotoxic, pro-inflammatory profile. (4) Finally, this effect of extracellular HSP110 on macrophages seems to implicate TLR4. These results together with the fact that colorectal tumor biopsies with HSP110 high were infiltrated with macrophages with a pro-tumoral profile while those with HSP110 low were infiltrated with macrophages with a cytotoxic profile, suggest that the effect of extracellular HSP110 function on macrophages may also contribute to the poor outcomes associated with HSP110 expression.